Oxidative stress response to aerobic exercise: Comparison of antioxidant supplements - Bloomer, R. J.; Goldfarb, A. H.; McKenzie, M. J. (Medicine & Science in Sports & Exercise, 2006)
Abstract: Purpose: To compare the effects of two antioxidant formulas on biomarkers of oxidative stress before and after aerobic exercise.